Creative Clinical Teaching In The Health Professions - Melrose, Sherri; Park, Caroline; Perry, Beth (Open textbook library., 2015)
This peer reviewed e-book is a must-read for nurses and other health professionals who strive to teach with creativity and excellence in clinical settings. Each chapter presents current evidence informed educational practice knowledge. Each topic is also presented with text boxes describing ‘Creative Strategies' that clinical teachers from across Canada have successfully implemented. For those who are interested in background knowledge, the authors provided a comprehensive literature base. And, for those interested mainly in 'what to do,' the text box summaries offer step-by-step directions for creative, challenging activities that both new and experienced instructors can begin using immediately.